Risk of cardiac implantable device malfunction in cancer patients receiving proton therapy: an overview - Mirzaei, Milad; Rowshanfarzad, Pejman; Gill, Suki; Ebert, Martin A.; Dass, Joshua (Frontiers in Oncology, 2023)
Age is a risk factor for both cardiovascular disease and cancer, and as such radiation oncologists frequently see a number of patients with cardiac implantable electronic devices (CIEDs) receiving proton therapy (PT). CIED malfunctions induced by PT are nonnegligible and can occur in both passive scattering (PS) and pencil beam scanning (PBS) modes. In the absence of an evidence-based protocol, the authors emphasise that this patient cohort should be managed differently to electron-and photonexternal beam radiation therapy (EBRT) patients due to distinct properties of proton beams. Given the lack of a PT-specific guideline for managing this cohort and limited studies on this important topic; the process was initiated by evaluating all PT-related CIED malfunctions to provide a baseline for future reporting and research.In this review, different modes of PT and their interactions with a variety of CIEDs and pacing leads are discussed. Effects of PT on CIEDs were classified into a variety of hardware and software malfunctions. Apart from secondary neutrons, cumulative radiation dose, dose rate, CIED model/manufacturer, distance from CIED to proton field, and materials used in CIEDs/pacing leads were all evaluated to determine the probability of malfunctions. The importance of proton beam arrangements is highlighted in this study.Manufacturers should specify recommended dose limits for patients undergoing PT. The establishment of an international multidisciplinary team dedicated to CIED-bearing patients receiving PT may be beneficial.